The Effectiveness of Human Resource Management in Improving the Quality of Madrasah Aliyah Nurul Muttahidah Pinotu - Putri, Musdalipah; Munawarsya, Muzawir; Santika, Santika (Idarah (Jurnal Pendidikan dan Kependidikan), 2024)
Human resource management (HRM) is an essential field within organizations that encompasses individuals' relationships and roles in achieving a company's or institution's objectives. HRM is especially important in educational institutions because it involves balancing educators' needs with the institution's capabilities. This study uses a descriptive qualitative method and a field approach to observe the effectiveness of Islamic education management in improving the quality of education at MA. Nurul Muttahidah Pinotu. The research findings suggest that human resource management, encompassing activities such as planning, organizing, implementing, and controlling, has a substantial impact on improving the quality of education. Furthermore, the school principal's leadership plays a crucial role in effectively coordinating and inspiring teachers, as well as in creating a curriculum that is both pertinent and groundbreaking. In addition, the recruitment and selection of educators, as well as the training and professional development of teachers, also play a significant role in enhancing the quality of education. Furthermore, the implementation of performance standards, evaluation, and constructive feedback is essential for effective teaching and achieving positive student learning outcomes. The successful implementation of efficient Human Resource Management (HRM) practices at MA Nurul Muttahidah Pinotu has resulted in notable enhancements in the performance of both teachers and staff. These improvements have been facilitated through the implementation of diverse initiatives, including training programs and opportunities for professional development.